Pre-flight exercise and bone metabolism predict unloading-induced bone loss due to spaceflight - Gabel, Leigh; Liphardt, Anna-Maria; Hulme, Paul A.; Heer, Martina; Zwart, Sara R.; Sibonga, Jean D.; Smith, Scott M.; Boyd, Steven (British Journal of Sports Medicine, 2021)
Objectives: Bone loss remains a primary health concern for astronauts, despite in-flight exercise. We examined changes in bone microarchitecture, density and strength before and after long-duration spaceflight in relation to biochemical markers of bone turnover and exercise. Methods: Seventeen astronauts had their distal tibiae and radii imaged before and after space missions to the International Space Station using high-resolution peripheral quantitative CT. We estimated bone strength using finite element analysis and acquired blood and urine biochemical markers of bone turnover before, during and after spaceflight. Pre-flight exercise history and in-flight exercise logs were obtained. Mixed effects models examined changes in bone and biochemical variables and their relationship with mission duration and exercise. Results: At the distal tibia, median cumulative losses after spaceflight were -2.9% to -4.3% for bone strength and total volumetric bone mineral density (vBMD) and -0.8% to -2.6% for trabecular vBMD, bone volume fraction, thickness and cortical vBMD. Mission duration (range 3.5-7 months) significantly predicted bone loss and crewmembers with higher concentrations of biomarkers of bone turnover before spaceflight experienced greater losses in tibia bone strength and density. Lower body resistance training volume (repetitions per week) increased 3-6 times in-flight compared with pre-spaceflight. Increases in training volume predicted preservation of tibia bone strength and trabecular vBMD and thickness. Conclusions: Findings highlight the fundamental relationship between mission duration and bone loss. Pre-flight markers of bone turnover and exercise history may identify crewmembers at greatest risk of bone loss due to unloading and may focus preventative measures.
CRIS-Team Scopus Importer:2021-03-05
Keywords: biochemistry; biomechanics; bone; exercise; osteoporosis